2019
DOI: 10.1080/13102818.2019.1671222
|View full text |Cite
|
Sign up to set email alerts
|

Production of saponins from in vitro cultures of Astragalus glycyphyllos and their antineoplastic activity

Abstract: In the last decade the need of plant-derived cytotoxic compounds exceeds the possibilities for obtaining them from naturally grown sources. In vitro plant biotechnology offers a unique and often invaluable alternative for production of complex biologically active substances without harming the flora. Astragalus glycyphyllos L. (Fabaceae) is a plant native to Bulgaria that has been reported to contain triterpenoid saponins and flavonoids. It is used in folk medicine as an antihypertensive, diuretic, anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…In DEAG, the main saponin (S1) was further used for the quantitative analytical marker. The quantitative analysis established that DEAG contained 3.12% total saponins, expressed as S1 [23]. The assay of PSM showed that it had 50.52% total saponins as the same marker [23].…”
Section: Phytochemistry Of Deag Psm and Saponins S1 S3 S9mentioning
confidence: 93%
“…In DEAG, the main saponin (S1) was further used for the quantitative analytical marker. The quantitative analysis established that DEAG contained 3.12% total saponins, expressed as S1 [23]. The assay of PSM showed that it had 50.52% total saponins as the same marker [23].…”
Section: Phytochemistry Of Deag Psm and Saponins S1 S3 S9mentioning
confidence: 93%
“…For the individual analysis of rutin and camelliaside a method, previously described (Shkondrov et al 2019) was applied. The total flavonoid content was determined by a gradient elution: 0 to 3 min 83% (A), 3 to 7 min 80% (A), 7 to 10 min 70% (A), 10 to 20 min 50% (A), 20 to 25 min 40% (A), 25 to 28 min 30% (A), 30 to 35 min 0% (A), 35 to 38 min 90% (A).…”
Section: Chromatographic Methodsmentioning
confidence: 99%
“…For the purpose of the analysis, those samples were diluted in 80% methanol to reach concentration of 500 µg/mL. The extraction of the plant material for individual quantitation of rutin and camelliaside A was performed as reported before (Shkondrov et al 2019). The extracts were kept at -18 °C, before the LC-HRESIMS analysis.…”
Section: Extraction Of In Vitro Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since anti-cancer chemotherapeutic agents damage normal cells, significant efforts have been made recently to identify natural compounds and related synthetic agents to prevent the development and recurrence of cancers (Greenwell and Rahman, 2015). Medicinal plants have been discovered and used in traditional medicine practices (Ahn, 2017), and remain as the basis of modern medicine (Shkondrov et al, 2019;Berezutskii et al, 2020;Borah and Banik, 2020;Darvishi et al, 2020). Numerous phytochemicals with potential or established biological activity have been identified (Ahn, 2017), and several anti-cancer chemotherapeutic drugs have been identified and isolated from medicinal plants (Borah and Banik, 2020).…”
Section: Research Articlementioning
confidence: 99%